Estudio y diseño de una red mpls para las dependencias externas ubicadas en la Región 7 de la Universidad Nacional de Loja. - Jiménez Macías, Gabriel Marcelo (2017)
This work focuses in the study and design of the network using the multiprotocol label switching (MPLS) to the interconnection of the external dependencies of the Universidad Nacional de Loja (UNL) located in the Region 7, this project that has been proposed by the Unidad de Telecomunicaciones e Información (UTI), a department own to the UNL. The network topology was designed for this interconnection, which was evaluated in test of performance, reliability, security, and fault recovery through a free network graphic simulator (GNS3). Through this simulator, it was possible to implement different routing protocols and to deploy the tag switching on which MPLS is based. The cost-benefit ratio of the edge routers that will allow the physical implementation of the MPLS network, through different network equipment manufacturers, and the bandwidth capabilities that MPLS service providers can the links of the central building of the UNL to the external dependencies. The commands entered in the routers were defined and appended to carry out the implementation of the MPLS network design in the infrastructure of the data network of the UNL, since it is the objective of the UTI to implement this project. Key words: MPLS, VPN